Brief State Rumination Inventory (BSRI): A Standardization Study for Turkish Speaking Populations - Altan-Atalay, Ayse; Kiziloz, Burcu Kaya; Donger, Ilayda; Demiray, Dilek (Springer/Plenum Publishers, 2020)
Rumination, which is a form of repetitive negative thinking, has been suggested as a variable associated with elevated risks for depression. Current research conceptualizes rumination as a dispositional entity but has neglected its more state-based forms, which may also be equally related to emotional disorders. Brief State Rumination Inventory (BSRI) is a psychometrically sound measure of state rumination, demonstrated to be sensitive to situational changes in rumination. The current study aims to examine the psychometric characteristics of the Turkish form of BSRI. Results of the first study replicated the single factor structure of the original version of BSRI in a group of 192 Turkish speaking adults between ages 18 and 65. Moreover, the Turkish version of BSRI yielded satisfactory levels of internal consistency and construct validity indicated by significant associations with measures of repetitive negative thinking, avoidant coping, and psychological distress. Study 2 examined the sensitivity of BSRI to momentary changes in rumination to assess the criterion validity of the Turkish form of BSRI, by examining its sensitivity to a rumination induction procedure in 66 university students (39 women). Together, these results suggest that the Turkish version of BSRI is a psychometrically reliable tool which is appropriate for the assessment of state rumination in Turkish speaking populations.
Keywords: Brief State Rumination Inventory; Reliability; Validity